MOTIVASI MAHASISWA DALAM MENJAGA KEBERSIHAN LABOR BOGA FAKULTAS PARIWISATA DAN PERHOTELAN UNIVERSITAS NEGERI PADANG - Dhaifina, Dhaifina; Silfeni, Silfeni; Abrian, Youmil (Journal of Home Economics and Tourism, 2017)
This research originated from the students who are not concerned with thecleanliness of catering laborers of the Faculty of Tourism and Hospitality StateUniversity of Padang. The purpose of this study is to describe how the intrinsicmotivation and extrinsic motivation of students in maintaining the cleanliness ofthe catering laboratory of the Faculty of Tourism and Hospitality State Universityof Padang. The research type is descriptive quantitative. The population of thisresearch are students who are and have been using labor catering Faculty ofTourism and Hospitality State University of Padang, as much as 558 people. Thesampling in this study is proposional random sampling as many as 85 people. Thedata collection are done by questionnaires using the scale of likert and has beentested the validity and reliability. This research result indicates that overall thestudents motivation in maintaining the cleanliness of the catering laboratory ofthe Faculty of Tourism and Hospitality State University of Padang 57.6% of therespondents declared as good, 30.6% of the respondents declared as enough and11,8% declared as very good.Keywords: Intrinsic Motivation, Extrinsic Motivation